2020
DOI: 10.1088/1755-1315/584/1/012062
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the impact of the COVID-19 pandemic on air emissions indicators of climate change originating from solid waste management in coastal settlements

Abstract: COVID-19 was first reported in Indonesia on March 2, 2020. Several actions have been taken, such as limiting population mobility and prohibiting almost all activities that can be avoided. This policy has environmental consequences, especially the amount of solid waste generation. This study provides a view of the effect of COVID-19 on the amount of solid waste generation and composition in coastal settlements, the impact on air quality which has implications for climate change, and provides the most efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Last but not least, air pollution or emission was also an important area of study, with a report that the use of life cycle assessment (LCA) [32] revealed a decrease in COVID-19 related wastes, with reported reductions in and methane and carbon dioxide emissions, as well as DOC (dissolved organic carbon, or solid waste). In addition, in early 2020 when COVID-19 was only a few months old, there are several publications related to solid, air, and water pollution, such as an analysis using SNI 19-3964-1994 showing reduction of solid waste and air emissions during COVID-19 [2], and also a review of coronavirus temperature dependence and survival in sewage water with recommendations for plumbing systems for COVID-19 [33]. However, as the virus evolves and global society prepares for the new normal, the aforementioned publications from the early days of COVID-19 are not considered to fully reflect the current conditions as the virus evolves and global society prepares protocols for a new normal.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Last but not least, air pollution or emission was also an important area of study, with a report that the use of life cycle assessment (LCA) [32] revealed a decrease in COVID-19 related wastes, with reported reductions in and methane and carbon dioxide emissions, as well as DOC (dissolved organic carbon, or solid waste). In addition, in early 2020 when COVID-19 was only a few months old, there are several publications related to solid, air, and water pollution, such as an analysis using SNI 19-3964-1994 showing reduction of solid waste and air emissions during COVID-19 [2], and also a review of coronavirus temperature dependence and survival in sewage water with recommendations for plumbing systems for COVID-19 [33]. However, as the virus evolves and global society prepares for the new normal, the aforementioned publications from the early days of COVID-19 are not considered to fully reflect the current conditions as the virus evolves and global society prepares protocols for a new normal.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…On the other hand, from the environmental point of view, the COVID-19 cases in Indonesia bring a significant change in terms of waste generation and waste management. It is reported that in the early days of outbreak, COVID-19 serendipitously reduced air pollution and emissions [2]. However, after around two years of the pandemic, there are extraordinary increases in medical wastes (face masks and personal protection equipment (PPE), gloves, goggles) not just in hospitals [3], but also in bodies of water [4].…”
Section: Introductionmentioning
confidence: 99%